Investigation of Lubricating Oil and Exhaust Valve Deposit Formation Using Blend Fuels in CI Engine - Faheem Ahmed Solangi; Aqeel Ahmed Bhutto; Altaf Alam Noonari; Muhammad Kashif Abbasi; Azhar Hussain Shah; Ali Murtaza Ansari; Ali Raza Solangi (Penerbit Universiti Kebangsaan Malaysia, 2025)
Based on the fi ndings of short-term research, biofuels are determined to be an acceptable replacement for petroleum diesel fuel. Extended research using these kinds of oils as fuel identifi ed issues with engine wear and upkeep. A 200- hour test was conducted on a single-cylinder compression ignition engine to examine the eff ects of fueling on engine longevity. This research work was carried out to investigate the long-term endurance test of DF100 (diesel fuel) as the base fuel, and blended fuels: DF95WCO5 (5% waste cooking oil and 95% DF), and DF65WCO20Pe15 (20% waste cooking oil, 65% DF, and 15% n-pentanol) through single-cylinder compression ignition (CI) engine. Further, the effects of DF100, DF95WCO5% and DF65WCO20Pe15 on exhaust valve surface deposits were also investigated. The SEM and EDS analysis showed that DF95WCO5 has a higher concentration of carbon deposits around the exhaust valve surface as compared to DF100 and DF65WCO20Pe15. Further, ternary blend fuel had minimal carbon deposits on the exhaust valve as compared to as compared to remaining both. This evidenced that the addition of pentanol significantly reduced the carbon deposition on the exhaust valve surface. About DF, DF95WCO5, and DF65WCO20Pe15, the percentage of carbon layer on exhaust valve surfaces is 44.67%, 45.42%, and 16.01%, respectively. For the fuel DF65WCO20Pe15, there was very little exhaust valve deposit formation during experimental examination. The ternary blend fuel also observed less concentration of Iron, Copper, Nickel and wear debris concentration as compared to DF100 and DF95WCO5.